2022
DOI: 10.3390/nano12060977
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Aggregation and Thermophoretic Particle Deposition Process in the Flow of Micropolar Nanofluid over a Stretching Sheet

Abstract: The purpose of this research is to investigate the consequence of thermophoretic particle deposition (TPD) on the movement of a TiO2/water-based micropolar nanoliquid surface in the existence of a porous medium, a heat source/sink, and bioconvection. Movement, temperature, and mass transfer measurements are also performed in the attendance and nonappearance of nanoparticle aggregation. The nonlinear partial differential equations are transformed into a system of ordinary differential equations using appropriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Subsequently, ( ) Au nanomaterials raise the thermal distribution to demolish cancer cells. Yu et al [10] demonstrated the influence of nanomaterials formation, thermophoretic mass transport, and permeable media on the flow of microorganism micropolar fluid through ( ) TiO 2 nanomaterials past a stretchable surface driven to heat source/sink. They addressed the result with and without the noticeable of nanomaterials formation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, ( ) Au nanomaterials raise the thermal distribution to demolish cancer cells. Yu et al [10] demonstrated the influence of nanomaterials formation, thermophoretic mass transport, and permeable media on the flow of microorganism micropolar fluid through ( ) TiO 2 nanomaterials past a stretchable surface driven to heat source/sink. They addressed the result with and without the noticeable of nanomaterials formation.…”
Section: Introductionmentioning
confidence: 99%
“…26,27 Alternative plasmonic materials, such as nitrides or carbides, with clear advantages in terms of cost, chemical/thermal stability, hardness, and photon−phonon coupling, 28−32 over their silver, gold, or graphene counterparts, 35 remain underexplored for the photo-thermal conversion in nanofluids, despite their plasmonic nature and good absorption efficiencies. 33,34 While the nanofluid design has largely focused on the solid fraction, both in terms of overall thermal conductivity and photothermal response, 36,37 the liquid fraction plays a critical role in heat diffusion and advection. Specifically, the solvent's thermal diffusivity influences the spatial and temporal propagation of heat across the nanofluid.…”
Section: ■ Introductionmentioning
confidence: 99%
“…While the nanofluid design has largely focused on the solid fraction, both in terms of overall thermal conductivity and photothermal response, , the liquid fraction plays a critical role in heat diffusion and advection. Specifically, the solvent’s thermal diffusivity influences the spatial and temporal propagation of heat across the nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of thermophoresis and Brownian motion, third-grade fluid parameters, micro-polarity, induced magnetic field, and micro-inertia density on the stream of an electrically conductive nanofluid migration towards an exponentially stretchable sheet was analyzed by Awan et al [10]. Yu et al [11] scrutinized the analysis of thermophoretic particle deposition, porous medium, and nanoparticle aggregation on the movement of a bioconvection micropolar fluid comprising titanium dioxide nanoparticles over a stretched sheet subject to a heat source/sink. They discussed the outcomes with and without the appearance of nanoparticle aggregation.…”
Section: Introductionmentioning
confidence: 99%